Investigating Off-Site Construction Methods in Indian Cities to Reduce Costs and Time in Housing Construction - Varsha Undara; Kranti Kumar Myneni (Current Approaches in Engineering Research and Technology Vol. 9, 2024)
There is a large need for urban housing based on the existing pace of expansion of Indian cities and their projected future growth. India wants to provide everyone with decent, safe, and cheap housing by 2030, yet there are currently 20 million fewer homes than what is needed. Traditional building methods have many disadvantages when trying to meet such high expectations in a short amount of time. These disadvantages include increased pollution, waste during construction, worker safety, and more, all of which drive up project costs and completion times. By moving all hindering activities to a controlled setting, offsite strategies can help lessen or prevent many of these negative impacts. Here, the construction method that is most appropriate and practical for contrasting traditional construction, composite construction, and offsite construction was determined. After that, the various off-site construction methods that are accessible were assessed and, after calculating the associated expenses and times, the most practical option was determined. Utilizing technical, manufacturer specifications, on-site performance, and literature as a basis, AHP analysis was used to do this. Ultimately, by determining the most appropriate off-site method for building mass housing in low- to medium-rise buildings, it was concluded that by selecting GFRG, the overall cost and duration of building housing on site was lowered, and it may facilitate the timely and economical completion of construction projects that best meet the expanding demands of urban areas.